2018
DOI: 10.1158/1055-9965.epi-17-0912
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer Burden and Opportunities for Prevention in a Safety-Net Healthcare System

Abstract: Among engaged patients, strategies to increase screening and follow-up of abnormal screening tests could prevent over 80% of cervical cancer cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 33 publications
5
23
0
Order By: Relevance
“…Findings from this population-based study are comparable to those from similar studies conducted in managed care health plan setting, a safety net system and state-wide evaluation that found proportions of women without screening of about 50%, 60%, and 64%, respectively. 6,7,11 Like similar studies, this study found that screened women had higher incomes and were more likely to be insured than unscreened women. Significant disparities in cervical cancer screening exist for women who live in poverty, have limited access to care, or are racial/ethnic minorities.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Findings from this population-based study are comparable to those from similar studies conducted in managed care health plan setting, a safety net system and state-wide evaluation that found proportions of women without screening of about 50%, 60%, and 64%, respectively. 6,7,11 Like similar studies, this study found that screened women had higher incomes and were more likely to be insured than unscreened women. Significant disparities in cervical cancer screening exist for women who live in poverty, have limited access to care, or are racial/ethnic minorities.…”
Section: Discussionsupporting
confidence: 74%
“…10 In this study, the dates in the medical records were used to classify women as "screened for cervical cancer" if they had a Pap test (with or without an HPV test) 6 months to 5 years before the date of diagnosis. This 6-month cutoff is a timeframe used by similar studies, 5,11 and assumes that Pap tests within 6 months would most likely represent follow-up testing to confirm abnormal results rather than screening. 10 Women were classified as unscreened if she had no screening in the 5-year timeframe or if she had a Pap test less than 6 months from her diagnosis.…”
Section: Dependent Variablesmentioning
confidence: 99%
See 3 more Smart Citations